Voluntary exercise attenuates inflammaging in mice - Melo-Miranda, Rita (2023)
Aging, one of the biggest health challenges of our time, is accompanied by numerous events, including an increase in inflammation levels (a process known as “inflammaging”), intestinal permeability, and dysbiotic alterations in the intestinal microbiota. Gut bacterial dysbiosis contributes to aging by increasing gut permeability and giving rise to systemic inflammation, thus feeding this positive feedback loop. Given the central role of inflammation in this interplay leading to aging, we aimed at dissecting its effect in microbiota evolution and whether it could be involved in pathobiont selection. To modulate the rate of inflammaging we sought to expose middle-aged mice to voluntary wheel running (for 16 weeks), which has been widely reported as anti-inflammatory. The rise in inflammation is still subtle at this age, allowing us to track its progression until old age and act preventatively. We found that, after 16 weeks of voluntary exercise, trained mice showed a less pronounced increase in the systemic levels of several pro-inflammatory cytokines when compared to controls, which remained sedentary throughout their lives. Of note, IL-6 production, whose increase has been extensively associated with aging, was lower in trained mice as compared to controls. Furthermore, trained mice showed higher muscle mass and strength and slower progression in frailty, compatible with the attenuation in development of age-related signs. We expect that differences in inflammation levels will impact microbiota evolution, potentially revealing differentially abundant bacteria and distinctive adaptive patterns among trained and sedentary mice. Moreover, we hypothesize that bacterial signatures found in trained mice will resembled those of younger, non-inflamed mice. Ultimately, this work may unravel new cues on the close association between the host’s inflammatory status and its bacterial inhabitants during aging as well as hint at bacterial shifts potentiated by exercise which may be important to healthy aging.